PARTISIPASI POLITIK PEMILIH PEMULA DALAM PEMILIHAN UMUM (PEMILU) - Benben Fathurokhman (Journal of Research and Development on Public Policy, 2022)
Indonesian elections are a real expression of democracy and a vehicle for the people to declare their sovereignty over the state and government. Elections are based on Pancasila and the 1945 Constitution of the Republic of Indonesia. Elections are held in the Unitary State of the Republic of Indonesia (NKRI) based on the principles of direct, universal, free, confidential, honest and fair elections. Political participation in a democratic country is an indicator of the implementation of the highest legitimacy of state power by the people (people's sovereignty), which is manifested in participation in democratic parties (elections). It can be said that general elections are one of the means of democracy and a manifestation of people's sovereignty, to produce representatives and leaders who are ambitious, competent and responsible for the welfare of the people. A very interesting group of voters to follow and learn more about is first-time voters. New voters are voters who are voting for the first time in an election. The purpose of this research is to find out the forms of political participation of new voters in elections, the factors that support the political participation of new voters in elections, and the factors that hinder the political participation of new voters in elections. The writing method used in this journal article is a literature review supported by relevant research. New voters are expected to be more actively involved in political activities, dividing their time between studying.